Factors Affecting Employee Performance PT Karya Pak Oles Tokcer Production Division Denpasar - Ginting, Casya Nova Nitali; Sudarma, Made; Dewi, Ida Ayu Listia (JURNAL MANAJEMEN AGRIBISNIS; Vol 11 No 01 (2023): Jurnal Managemen Agribisnis, 2023)
The purpose of this study was to determine how the effect of compensation, work motivation and work environment on the performance of employees of PT Karya Pak Oles Tokcer Denpasar Production Division. The number of samples in this study were 30 respondents, using the saturated sampling method (census). Collecting data with interviews, documentation and questionnaires where the variables are measured by giving a score of 1-3. Data analysis is modeled into SEM (Structural Equation Modeling) model using smartPLS.3.0 software. The results showed that compensation, work motivation and work environment had a positive and significant effect on employee performance. The results of the compensation variable are seen from the t-statistics value > T table (1.96) of 4.771 and the original positive sample is 0.523, work motivation which can be seen from the t-statistics value > T table (1.96) is 2.475 and obtained the original positive sample was 0.308 in the work environment which can be seen from the t-statistic value > T table (1.96) of 2,597 and the original sample positive was 0.402. Based on the original sample value, the research shows that the factor that most influences employee performance is compensation.